Work Stress and Spirituality in Diabetes Mellitus Self-Management - Kusnanto, Kusnanto; Satriyaningarum, Nyuasthi Genta; Pratiwi, Ika Nur; Arifin, Hidayat (International Journal of Psychosocial Rehabilitation, 2020)
The problem in diabetes mellitus self-management (DSME) a productive working adult often faces is that diabetes can be caused by high work activities and low spirituality. The purpose of this study was to determine the relationship between work stress and spirituality in DSME. A descriptive correlation design with a cross-sectional approach was used. A total of 101 respondents in one health primary care facility in East Java Province participated in this study. The respondents were acquired by stratified random sampling. The independent variables were work stress and spirituality. The dependent variable was diabetes mellitus self-management. The data were obtained through several instruments (Brief Work stress Questionnaire; Daily Spiritual Experience Scale; and Diabetes Self- Management Questionnaire). The data were analyzed using Spearman Rho and regression logistic with a value of α≤0.05. The result showed a relationship between work stress (p = 0.008) and spirituality (p = 0.000) with DSME. The multivariate test results showed that spirituality was the most dominant (p = 0.000) related variable. Conclusion: controlling work stress and increasing spirituality are important components that need to be considered to improve DSME.